2013
DOI: 10.1016/j.econmod.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Real convergence in Europe: A cluster analysis

Abstract: In this paper we analyse real convergence in GDP per worker in the EU member states.The aim is to test whether there is evidence of club convergence in the EU, i.e. divergence in GDP per worker. Evidence in favour of cluster or club convergence may be an indication of significant productivity divergences between countries, which may also explain the current turmoil in the euro zone. The results show evidence of different economic growth rates within Europe, which also converge to different steady states, imply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 18 publications
7
84
0
11
Order By: Relevance
“…The functions plotted in Figures 1 and 2 are the arithmetic averages of the values provided in the respective columns of Tables 2 and 3. These results are in line with some other studies that confirm the existence of divergence tendencies in Europe in the last years (see, e.g., Mucha, 2012;Stanisic, 2012;Borsi and Metiu, 2013;Monfort et al, 2013). For example, the study by Matkowski et al (2016b) showed -with the use of the σ convergence concept -that in 2009 and 2010, income differences among the 26 EU countries increased.…”
Section: Empirical Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The functions plotted in Figures 1 and 2 are the arithmetic averages of the values provided in the respective columns of Tables 2 and 3. These results are in line with some other studies that confirm the existence of divergence tendencies in Europe in the last years (see, e.g., Mucha, 2012;Stanisic, 2012;Borsi and Metiu, 2013;Monfort et al, 2013). For example, the study by Matkowski et al (2016b) showed -with the use of the σ convergence concept -that in 2009 and 2010, income differences among the 26 EU countries increased.…”
Section: Empirical Analysissupporting
confidence: 80%
“…There are also studies that suggest the existence of convergence clubs in the EU (e.g. Borsi and Metiu, 2013;Monfort et al, 2013;Gligoric, 2014). The book by Jozwik (2017) presents the analysis of convergence at the national and regional levels, focusing on institutional changes due to systemic transformation, economic integration, and the cohesion policy.…”
Section: Real Convergencementioning
confidence: 99%
“…This result casts doubt on the rather optimistic view which suggests that new countries can simply be added to the EU and strengthening business cycle synchronisation with the entire EU. Monfort et al (2013) show that real convergence in the EU has occurred in the form of club convergence, meaning that the EU countries converge to group-specific long-run growth rather than to a common EU steady-state. According to these findings, the economic integration process in the EU has been unable to reduce the basic structural divergences among countries.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, our paper takes a step forward with respect to Monfort et al (2013), who conduct a similar analysis, but based on labour productivity. Not only do we identify the existence of clusters, but we also ascribe the identified convergence clubs to specific components of the RULCs, with labour productivity decomposed into capital intensity and technological components.…”
Section: Rulc =mentioning
confidence: 99%